Influence of a complex mycotoxin detoxifier on growth performance, liver health, inflammation, and redox status of broilers fed a diet contaminated with multiple mycotoxins - Nampetch Puengpong; Thaweesak Songserm; Konkawat Rassmidatta; Joan Torrent; Alireza Khadem; Arnau Vidal; Christos Gougoulias; Nithikarn Chanaksorn; Kazeem D. Adeyemi; Yuwares Ruangpanit (PLoS ONE, 2026)
This study investigated the effects of a complex mycotoxin detoxifier (CMD) on growth performance, liver health, inflammation, and redox status of broilers fed a diet contaminated with multiple mycotoxins. A total of 432 one-day-old male Ross 308 broiler chicks were randomly allocated to one of three treatments, with eight replicates per dietary group for 37 d. The treatment included: a basal diet without mycotoxin, positive control, PC; a basal diet contaminated with 80 ppb Aflatoxin + 900 ppb fumonisins + 30 ppb deoxynivalenol + 80 ppb Zearalenone, negative control, NC or NC supplemented with CMD (sodium bentonite, sepiolite, yeast cell wall, and β-glucans) at 1 and 0.5 kg/ton in the starter and finisher diet respectively. Compared with the PC and CMD groups, NC birds showed higher feed intake and poorer feed efficiency during days 1–10 (p < 0.05), although these differences were not observed thereafter. Newcastle disease antibody titer was reduced in NC birds but restored by CMD supplementation (p < 0.05). Birds receiving CMD also exhibited higher IL-10 concentrations than both PC and NC birds (p < 0.05). Furthermore, CMD supplementation reduced macroscopic fatty liver scores and liver inflammation (histopathological lesions) compared with the NC group (p < 0.05). In conclusion, dietary exposure to multiple mycotoxins caused only transient impairment of growth performance but adversely affected immune response and liver health. Supplementation with CMD at 1.0 and 0.5 kg/ton during the starter and finisher phases, respectively, alleviated several of these adverse effects in broiler chickens.